IMPORTANCE OF EARLY INTERVENTION BY THE PHYSIOTHERAPIST IN WHIPLASH SYNDROME - Quintana Arango, J E; Gonzalez Garcia, F (Cuestiones de Fisioterapia, 2002)
The goal of this research is to expose the importance of the early intervention of the physiotherapist on whiplash injuries and cervical sprains.This piece of work is based on prospective observational research using as subjects 87 car accident victims, which belong to different insurance companies, and assisted to our clinic for treatment.Different variables in relation to the accident were analyzed such as: if the victim wore a cervical collar, the number of days which the victim wore it, and the number of days which took that patient to receive treatment after the accident. The same process of treatment was applied to all of them with classic therapist methods.The data was registered every 10 days and finally analyzed using Microsoft Access program and SPSS. The following conclusions were made: The more days which the car accident victim wears the cervical collar, the more treatment he will need afterwards. The more days that go by until the patient receives treatment, the more treatment he will need.